MENYIASATI RUANG, MENEBAR KEDAMAIAN - Dedi Slamet Riyadi (Research and Development Center for Guidance for Religious Societies and Religious Services, the Research and Development and Education and Training Agency of the Ministry of Religious Affairs of the Republic of Indonesia (MORA), 2017)
To me, its nonsense—and very dangerous nonsens at that—all this talk of I’m Tajik and you’re Pashtun and he’s Hazara and she’s Uzbek. We’re all afghans, and that’s all that should matter. But when one group rules over the others for so long … there’s contempt. Rivalry. There is. There always have been. (Khaled Hosseini, A Thousand Splendid Suns)[1] [1] Khaled Hosseini, A Thousand Splendid Suns, Bloomsbury Publisihing, London, 2007, hlm. 117.